The weight balancing act and allostasis: Commentary on the Homeostatic Theory of Obesity - Emily Brindal; Gary Wittert (Health Psychology Open, 2016)
The current article provides commentary on the Homeostatic Theory of Obesity and associated Circle of Discontent. A strength of this theory is that it points to the requirement for multiple avenues of societal change, largely through policy and regulation. The current authors suggest consideration of allostasis, coping style and habituation in addition to the existing model. Incorporation of these into the Homeostatic Theory of Obesity may help to expand its explanatory power and associated avenues of intervention. Whatever else is done, it is likely that to meaningfully address the epidemic of obesity and associated chronic disease will require policy and regulation as well as targeted behavioural strategies aiming to reduce allostatic load.